2020
DOI: 10.3389/fmicb.2020.01904
|View full text |Cite
|
Sign up to set email alerts
|

Field Exploitation of Multiple Functions of Beneficial Microorganisms for Plant Nutrition and Protection: Real Possibility or Just a Hope?

Abstract: Bioproducts, i.e., microbial based pesticides or fertilizers (biopesticides and biofertilizers), should be expected to play an ever-increasing role and application in agricultural practices worldwide in the effort to implement policies concerned with sustainable agriculture. However, several microbial strains have proven the capacity to augment plant productivity by enhancing crop nutrition and functioning as biopesticides, or vice-versa. This multifunctionality is an issue that is still not included as a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 119 publications
0
14
0
1
Order By: Relevance
“…In fact, under the new European regulation on fertilizers (reg. 2019/1009), some microbialbased biostimulants have "multifunctional" features, including ISR, that are not taken into consideration (Table 1) [31]. Thereby, the authors argue for a consideration of the wider context and to harness available synergies whenever possible.…”
Section: Fostering Cooperation and Synergies Bridging The Gap Between Science And Industrymentioning
confidence: 99%
“…In fact, under the new European regulation on fertilizers (reg. 2019/1009), some microbialbased biostimulants have "multifunctional" features, including ISR, that are not taken into consideration (Table 1) [31]. Thereby, the authors argue for a consideration of the wider context and to harness available synergies whenever possible.…”
Section: Fostering Cooperation and Synergies Bridging The Gap Between Science And Industrymentioning
confidence: 99%
“…In particular, immobilized cell technologies are used to study the behavioral changes in cells of plant beneficial microorganisms as the immobilized state is the normal state of microorganisms in soil [64]. These methods are also involved in formulation of biofertilizers [15,65]. As stated by some earlier studies and further confirmed by many other works, the immobilization of cells offers a number of advantages, such as a greater number of cells in one volume unit, the possibility of easier continuous fermentation process, greater metabolic stability and activity, easier downstream operations [66][67][68][69] and, particularly in the field of formulation of biofertilizers, the slow release of cells in soil-plant systems and the possibility to combine different types of bioeffectors in one product [70][71][72].…”
Section: Immobilized-cell-based Fermentation Processesmentioning
confidence: 99%
“…However, it is also important to mention that only 10% of the soil microorganisms inhabiting zones surrounding plant roots can be cultivated, while the rest are declared uncultivable in standard media [13]. Bearing in mind the key role of soil microorganisms in sustainable agriculture and the concerns regarding crop quality and human health, as well as the problems of a growing human population in combination with climate change, the biotechnological approach in production and formulation of plant beneficial microorganisms should be in the focus of the scientific community [14][15][16]. Biotechnology offers a wide array of techniques leading to bioformulates: starting from selection of promising microbial strains, characterizing their morphological, physiological and biochemical properties, testing their activity under fermentation and soil conditions and, finally, formulating them into commercial products [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it is also essential to support the understanding of the mechanisms of biocontrol and to interpret the results of efficacy tests. Such analysis would be even more important when inocula with multifunctional properties or consortia of strains are tested [ 24 , 25 ] and also considering the new “holobiont” concept about the intergenomic associations of the plant-pest-bioinoculum relation [ 26 ]. Indeed, understanding how the inoculants may affect the soil ecosystem as well as soil key ecosystem service, remains a major challenge.…”
Section: Introductionmentioning
confidence: 99%